Consumer neuroscience: usability of brain imaging methods in marketing research - Vainio, Mikael (My University, 2015)
Consumer neuroscience (neuromarketing) is an emerging field of marketing research which uses brain imaging techniques to study neural conditions and processes that underlie consumption. The purpose of this study was to map this fairly new and growing field in Finland by studying the opinions of both Finnish consumers and marketing professionals towards it and comparing the opinions to the current consumer neuroscience literature, and based on that evaluate the usability of brain imaging techniques as a marketing research method. Mixed methods research design was chosen for this study. Quantitative data was collected from 232 consumers and 28 marketing professionals by means of online surveys. Both respondent groups had either neutral opinions or lacked knowledge about the four themes chosen for this study: benefits, limitations and challenges, ethical issues and future prospects of consumer neuroscience. Qualitative interview data was collected from 2 individuals from Finnish neuromarketing companies to deepen insights gained from quantitative research. The four interview themes were the same as in the surveys and the interviewees’ answers were mostly in line with the current literature, although more optimistic about the future of the field. The interviews also exposed a gap between academic consumer neuroscience research and practical level applications. The results of this study suggest that there are still many unresolved challenges and relevant populations either have neutral opinions or lack information about consumer neuroscience. The practical level applications are, however, already being successfully used and this new field of marketing research is growing both globally and in Finland.